The influence of debt policies, profitability and corporate social disclosures responsibility to tax agresivity - Afiyatul Khafifah (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - The research objective is to determine the effect of debt policy, profitability, and Corporate Social Responsibility (CSR) on tax aggressiveness in mining sector companies listed in the Indonesian Sharia Stock Index for the period 2014-2019.Method - The population of this study was 35 mining companies listed on the Indonesian Sharia Stock Index for 2014-2019. The sample selection in this study used purposive sampling method and 6 companies were selected. The data analysis used multiple linear regression analysis. Three tests were conducted; determinant coefficient test, simultaneous significant test, and partial regression test (T-Test).Result - The results show that debt policy (DAR) has a significant negative effect on tax aggressiveness, Profitability (ROA) has a significant negative effect on tax aggressiveness, and disclosure of Corporate Social Responsibility (CSR) has a significant negative effect on tax aggressiveness.Implication - Mining companies registered in the ISSI for the 2014-2019 period have proven that their tax aggressiveness is low, which means they are compliant with tax payments. However, on the other hand, the company must maintain and improve compliance in paying taxes.Originality - This study is the first study using a sharia mining company registered with the ISSI related to tax aggressiveness.